Social Media Based Marketing Strategy to Build a Positive Image - Fitri, Adelia; Daulay, Nurika Khalila (Yayasan Sembilan Pemuda Indonesia, 2025)
This research aims to describe and analyze the social media-based marketing strategies implemented by MTS Al-Washliyah Km 6 Medan in building a positive image of the institution amidst the increasingly competitive educational institution rivalry. In the digital era, social media has become a strategic means of conveying information, fostering communication, and strengthening the branding of Islamic education. This research employs a qualitative approach with data collection techniques through observation, in-depth interviews, and documentation involving social media managers, school principals, and related stakeholders. The results indicate that utilizing platforms such as Instagram, Facebook, and WhatsApp with educational content, promotional activities of the school, as well as testimonials from students and alumni. This strategy is effective in increasing the visibility of schools and shaping a positive perception of the quality of education and Islamic values in the community. This study fills a gap in the literature by examining how Islamic values are integrated into social media marketing for madrassas, a topic that has been less explored in existing research. The findings emphasize that social media marketing can be an important instrument in building a positive image of schools if implemented consistently, communicatively, and in accordance with the characteristics of the audience.